The Influence of Principal Academic Supervision on Teacher Performance - Suryanto, Suryanto; Wicaksono, Luhur; Waruwu, Marinu (Indonesian Journal of Education and Mathematical Science, 2025)
The improvement of teacher performance in elementary schools is the focus of this study, which seeks to identify and prove the significant relationship between academic supervision by the principal and the enhancement of teaching effectiveness. The study involved 17 teachers from SD Negeri 51 Sungai Kunyit in the Sekadau Hilir District of Sekadau Regency, West Kalimantan Province, and employed a questionnaire instrument based on a Likert scale, using a quantitative approach and survey method. With a significance value of 0.000 ( 0.005) and a correlation of 65.2%, the results of the linear regression analysis revealed that academic supervision by the principal significantly influenced teacher performance. Improving teacher performance can be achieved through effective academic supervision, as emphasized by these findings. To improve the teaching process, support teachers' professional development, and enhance the quality of school programs and student achievements, it is recommended that principals strengthen their qualifications and supervisory competencies to provide more comprehensive guidance.